The effect of parents’ presence on improving personal and social behavior in children (4-16) during and after the home quarantine period during the Corona pandemic in Jordan - Algrair, Ahmad Nayel; Fayyad, Maysra Abdel-Raheem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the importance and impact of the presence of parents at home during the Corona pandemic-Covid-19, as they are responsible for raising children, as the study sample reached (368) parents and used a questionnaire of personal and social behavior (20) paragraphs distributed in two dimensions and designed specifically for the purposes of the current study and an appropriate degree of Honesty and constancy, and the results indicated the importance of the presence of parents with children during crises and the Corona pandemic crisis-Covid-19in particular, and the study showed an impact and improvement in the personal and social behavior of children during the quarantine period, and they showed more commitment and awareness than before, in addition to developments in the environmental dimension, the study and training studies the level of awareness of children in these crises and the phenomenon of study. Involving them in activities and tasks and interacting with them and not leaving them without monitoring their presence at home.